Jihadism & Governance in North-Syria: Comparing Islamism and Governance in Aleppo and Raqqa - Donker, Teije Hidde (PARTECIPAZIONE E CONFLITTO, 2022)
Does ideology shape jihadist attempts at implementing rebel governance? In this article, I argue that the distinctness of jihadist governance initiatives emerges from the type of challenges that jihadists face when attempting to implement a distinct form of governance. To support this argument, I focus on the provision of public services in rebel-controlled Aleppo and Raqqa between 2012 and 2016. Two distinctly jihadist challenges emerge from this narrative: The first is how to position a jihadist identity in relation to local and national identities; the second is how to balance popular representation and religious authority as a source of legitimation for governance decisions. The strategic responses to these challenges vary across time and space. A focus on distinct challenges provides an avenue to investigate the distinctness of jihadist groups’ attempts at rebel governance, while acknowledging their pluralist, multilayered and dynamic practices. The analysis builds on more than a hundred primary sources from Daesh, the Nusra Front, Ahrar al-Sham and relevant local jihadist actors, in addition to hundreds of sources from other governance related actors. It also draws on Arabic, English and French secondary sources and around thirty interviews with relevant actors and governance organizations.